A Philosophy of Beauty : Shaftesbury on Nature, Virtue, and Art - Gill, Michael B. (Book collections on Project MUSE., 2022)
An engaging account of how Shaftesbury revolutionized Western philosophy. At the turn of the eighteenth century, Anthony Ashley Cooper, the third Earl of Shaftesbury (1671-1713), developed the first comprehensive philosophy of beauty to be written in English. It revolutionized Western philosophy. In A Philosophy of Beauty, Michael Gill presents an engaging account of how Shaftesbury's thought profoundly shaped modern ideas of nature, religion, morality, and art--and why, despite its long neglect, it remains compelling today.Before Shaftesbury's magnum opus, Charactersticks of Men, Manners, Opinions, Times (1711), it was common to see wilderness as ugly, to associate religion with fear and morality with unpleasant restriction, and to dismiss art as trivial or even corrupting. But Shaftesbury argued that nature, religion, virtue, and art can all be truly beautiful, and that cherishing and cultivating beauty is what makes life worth living. And, as Gill shows, this view had a huge impact on the development of natural religion, moral sense theory, aesthetics, and environmentalism.Combining captivating historical details and flashes of humor, A Philosophy of Beauty not only rediscovers and illuminates a fascinating philosopher but also offers an inspiring reflection about the role beauty can play in our lives.